2019
DOI: 10.1071/en18162
|View full text |Cite
|
Sign up to set email alerts
|

Low-density polyethylene microplastics as a source and carriers of agrochemicals to soil and earthworms

Abstract: Environmental contextMicroplastics, long recognised as contaminants in aquatic ecosystems, are increasingly of environmental concern for terrestrial ecosystems. This study focuses on the potential of microplastics to act as carriers of agrochemicals and the subsequent effects on soil biota. The results indicate the need for further studies into how soil properties influence both the degradation of microplastics and their role as pollutant carriers. AbstractMicroplastics (MPs) are of environmental concern to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(28 citation statements)
references
References 67 publications
0
28
0
Order By: Relevance
“…[80][81][82] It has also been pointed out that plastics could act as carriers of inorganic and organic contaminants in the water-soil interface, releasing these contaminants into the environment and affecting soil (micro-)organisms, with adverse consequences for the food web. 83,84 As a result of increased environmental awareness, biodegradable, oxo-biodegradable, and compostable plastics have been proposed as environmentally friendly alternatives to conventional plastics. 85,86 However, the ecotoxicological implications of these materials are not well studied or they have sometimes been reported to have unanticipated problems such as low environmental degradation under realistic conditions.…”
Section: Microplastics: An Increasingly Important Environmental Issuementioning
confidence: 99%
See 1 more Smart Citation
“…[80][81][82] It has also been pointed out that plastics could act as carriers of inorganic and organic contaminants in the water-soil interface, releasing these contaminants into the environment and affecting soil (micro-)organisms, with adverse consequences for the food web. 83,84 As a result of increased environmental awareness, biodegradable, oxo-biodegradable, and compostable plastics have been proposed as environmentally friendly alternatives to conventional plastics. 85,86 However, the ecotoxicological implications of these materials are not well studied or they have sometimes been reported to have unanticipated problems such as low environmental degradation under realistic conditions.…”
Section: Microplastics: An Increasingly Important Environmental Issuementioning
confidence: 99%
“…80-82 It has also been pointed out that plastics could act as carriers of inorganic and organic contaminants in the water-soil interface, releasing these contaminants into the environment and affecting soil (micro-)organisms, with adverse consequences for the food web. 83,84…”
Section: Soil Biodiversity and Threatsmentioning
confidence: 99%
“…Environmental pollution by microplastics (MPs) and nanoplastics (NPs) has raised growing concerns in the last two decades, also as a result of the increasing evidences regarding the direct and indirect negative effects of such contaminants on both marine [1] and soil biota [2,3], and the potential of bioaccumulation and transfer to humans through the food chain. A vast and recent literature accounts for the role of microplastics (those within 0.1-5 mm size being typically considered) as accumulators and carriers of several persistent organic pollutants (POPs) and heavy metals, which can then affect aquatic organisms [4] as well as soils contaminated by MPs, e.g., through sludges from civil wastewater treatment plants [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Their ingestion of plastic particles not only may cause mechanical damage, inflammation and microbiota dysbiosis of intestinal tracts (Burgos‐Aceves, Cohen, Smith, & Faggio, 2018; Guzzetti, Sureda, Tejada, & Faggio, 2018; Jin et al., 2018; Lei, Liu, et al, 2018; Qiao et al., 2019; Savoca et al., 2019), but it could also induce oxidative and immune stress, metabolic disorders and detoxification suppression in other vital tissues, such as livers, gills and haemolymph (Lei, Wu, et al, 2018; Yu et al., 2018). Moreover, microplastics can act as carriers of other pollutants such as heavy metal and persistent organic pollutants (POPs), thereby strengthening their biotoxicity (Rodríguez‐Seijo, Santos, da Silva, Cachada, & Pereira, 2019). Additionally, some studies have indicated that the reproductive process of aquatic animals may be impaired by their exposure to microplastics (Pitt et al., 2018; Sussarellu et al., 2016).…”
Section: Introductionmentioning
confidence: 99%